Load Balancing In Clustered Network (International Journal of Engineering and Computer Science, 2014)
Network has lots of connections and the server has n number of requests to be handled. To reduce the work load of the server, we create subsequent sub servers and they are used to handle requests from clients. Each client can login and get their required information from the sub server. A report is generated for all the requests handled by the sub servers and the server maintains the log. A fully distributed load balancing algorithm is presented to scope with the load imbalance problem. DSBCA algorithm is compared against a centralized approach in a production system and a competing distributed solution presented in the literature. The Real time results indicate that our proposal is comparable with the existing centralized approach and considerably outperforms the prior distributed algorithm in terms of load imbalance factor, movement cost, and algorithmic overhead. The performance of our proposal implemented in the Ha-doop distributed file system is further investigated in a cluster environment. The main reason for the formation of such clusters is that clustered overlays enable their participants to find and exchange data relevant to their queries with less effort.